A Single Sfp-Type Phosphopantetheinyl Transferase Plays a Major Role in the Biosynthesis of PKS and NRPS Derived Metabolites in Streptomyces ambofaciens ATCC23877 - Bunet, Robert; Riclea, Ramona; Laureti, Luisa; Hôtel, Laurence; Paris, Cédric; Girardet, Jean-Michel; Spiteller, Dieter; Dickschat, Jeroen S.; Leblond, Pierre; Aigle, Bertrand (PLOS ONE, 2014)
The phosphopantetheinyl transferases (PPTases) are responsible for the activation of the carrier protein domains of the polyketide synthases (PKS), non ribosomal peptide synthases (NRPS) and fatty acid synthases (FAS). The analysis of the Streptomyces ambofaciens ATCC23877 genome has revealed the presence of four putative PPTase encoding genes. One of these genes appears to be essential and is likely involved in fatty acid biosynthesis. Two other PPTase genes, samT0172 (alpN) and samL0372, are located within a type II PKS gene cluster responsible for the kinamycin production and an hybrid NRPS-PKS cluster involved in antimycin production, respectively, and their products were shown to be specifically involved in the biosynthesis of these secondary metabolites. Surprisingly, the fourth PPTase gene, which is not located within a secondary metabolite gene cluster, appears to play a pleiotropic role. Its product is likely involved in the activation of the acyl- and peptidyl-carrier protein domains within all the other PKS and NRPS complexes encoded by S. ambofaciens. Indeed, the deletion of this gene affects the production of the spiramycin and stambomycin macrolide antibiotics and of the grey spore pigment, all three being PKS-derived metabolites, as well as the production of the nonribosomally produced compounds, the hydroxamate siderophore coelichelin and the pyrrolamide antibiotic congocidine. In addition, this PPTase seems to act in concert with the product of samL0372 to activate the ACP and/or PCP domains of the antimycin biosynthesis cluster which is also responsible for the production of volatile lactones.